The Transnational Role of Foreign Companies in the Upstream Sector of Oil and Gas in Indonesia: pre-Gross Split Mechanism - Yulida Nuraini Santoso (Global South Review, 2019)
This article aims to explain how and why foreign oil and gas companies carry influence over the government in the upstream oil and gas sector. It looks at the troubling issue of domination in Indonesia particularly before the Gross Split mechanism was introduced. From a transnational point of view, states and non-states continuously attempt to overpower the other to gain the most from this industry. Although the roles and obligations of foreign oil and gas companies are strictly regulated, domination is still visible in areas of cost recovery to add to the weak domestic market resulting in an asymmetric competition. Market failures have become increasingly alarming as liftings continue to fail to reach the national quota. Using the introduction of the Gross Split mechanism as a turning point, this article looks back at how transnationalism has translated into this sector. This article is of the view that the lack of effort to enrich knowledge bases, enforce the adoption of appropriate technology and prepare its domestic market for healthy competition, has brought it further away from addressing its underlying issues.